Everolimus and exemestane in long survival hormone receptor positive male breast cancer: case report. (December 2016) - Ballatore, Z.; Pistelli, M.; Battelli, N.; Pagliacci, A.; Lisa, M.; Berardi, R.; Cascinu, S.
Abstract Background Male breast cancer is a rare event, accounting for approximately 1% of all breast carcinomas. Although men with breast cancer had poorer survival when compared with women, data on prognosis principally derive from retrospective studies and from extrapolation of female breast cancer series. We reported the case of a very long survival patient. Case presentation A caucasian 42-year-old man underwent radical mastectomy with axillary dissection for breast cancer in 1993. Pathologic stage was pT4pN0M0 infiltrating ductal carcinoma of right breast without lymph nodes metastases. Biological characterization was not available. He received adjuvant treatment with chemotherapy, six cycles of cyclophosphamide, methotrexate and fluorouracil, then endocrine therapy with tamoxifen for 5 years and complementary radiotherapy. Then he began clinical-instrumental follow up. In May 1996, a computed tomography scan showed multiple lung metastases. Hereafter he received several oncologic treatment including seven chemotherapy and five endocrine therapy lines with two re-challenge of endocrine therapy. In October 2007 further lung progression was showed and a biopsy was performed to characterize the disease. Histological examination confirmed breast cancer metastases, immunohistochemistry showed positive staining for estrogen receptor, negative for progesterone receptor and human epithelial growth factor receptor 2, proliferative index was 21%. In April 2013, bone disease progression was evident and he received radiant treatment to sacral spine. In May 2014 an off-label treatment with exemestane and everolimus combination was approved by Ethics Committee of the Marche Region. The patient received treatment for 3 months with evident clinical benefit to subcutaneous lesions of the chest wall that were not visible nor palpable on physical examination after 1 month of treatment. Conclusion That is the case of long survival male breast cancer patient with luminal B subtype and no BRCA mutations. He achieved higher progression free survival with endocrine therapy creating the rationale for last line treatment with everolimus and exemestane combination. Attending conclusive results from ongoing studies, everolimus and exemestane should not be used routinely in male metastatic breast cancer patients, but taking into account for selected cases. At the best of our knowledge, this is the first case of male beast cancer treated with exemestane and everolimus combination.